AUTOMATED BASE OF SIMULATOR TRAINING MATERIALS FOR SPECIALITY «MAINTENANCE OF AIRCRAFT AND AIRCRAFT ENGINES» - V. A. Naida (Naučnyj Vestnik MGTU GA, 2016)
The article deals with methodical issues of development of the training materials automated base for conducting classes using a specialized simulator.